2013
DOI: 10.1007/s00468-013-0904-y
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and stem hydraulic traits in relation to growth, water use and fruit yield in Prunus avium L. cultivars

Abstract: Leaf and stem hydraulic traits in relation to growth, water use and fruit yield in Prunus avium L. cultivars

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…To the present day, the significance of adequate rootstock selection for the fruit plantation has been addressed in several research papers (Beckman and Lang, 2002;Webster, 2002b;Nimbolkar et al, 2016;Hrotkó and Rozpara, 2017). Identification of genetic material and understanding of plant properties responsible for the fruit production improvement, as well as the proper selection of rootstock that reduce vegetative growth and increase carbon allocation to reproduction, are considered of great importance (Peschiutta et al, 2013). Rootstocks enrich the cultivar with numerous traits, such as good anchorage, good radial and axial hydraulic conductivity, water use efficiency, soil's pest and disease resistance, improved tolerance to drought and high soil salinity (Gainza et al, 2015a;Ljubojević et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To the present day, the significance of adequate rootstock selection for the fruit plantation has been addressed in several research papers (Beckman and Lang, 2002;Webster, 2002b;Nimbolkar et al, 2016;Hrotkó and Rozpara, 2017). Identification of genetic material and understanding of plant properties responsible for the fruit production improvement, as well as the proper selection of rootstock that reduce vegetative growth and increase carbon allocation to reproduction, are considered of great importance (Peschiutta et al, 2013). Rootstocks enrich the cultivar with numerous traits, such as good anchorage, good radial and axial hydraulic conductivity, water use efficiency, soil's pest and disease resistance, improved tolerance to drought and high soil salinity (Gainza et al, 2015a;Ljubojević et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In cherry, they have also been found to reduce the meristematic activity of their growing shoots due to a change in the gene expression both in the scion and at the graft union level (Prassinos et al, 2009). Rootstock vigor can also affect productivity and quality of the production (Lang, 2000;Neilsen et al, 2016), due to variations in the hydraulic anatomy and in the water relations of the scion (Peschiutta et al, 2013), although crop load and thus leaf/fruit ratio, seems to be the major driver affecting fruit development and final fruit quality (Whiting and Lang, 2004;Neilsen et al, 2016). Regarding fruit quality, Gonçalves et al (2006b) showed how thanks to their better water status, vigorous rootstocks usually show a higher fruit size, also because the combination between autofertile cultivars and dwarfing rootstocks may induce excessive crop loads (Bassi 2005).…”
Section: Introductionmentioning
confidence: 99%